Gas and humidity sensing with quartz crystal microbalance (QCM) coated with graphene-based materials – A mini review - Fauzi, Fika; Rianjanu, Aditya; Santoso, Iman; Triyana, Kuwat (Sensors and actuators. A. Physical., 2021)
[Display omitted] •The used of graphene-based materials as QCM sensing active layer for gas and humidity sensors are studied.•The sensing performance of the graphene-based materials to detect specific gas and humidity are discussed in detail.•The probable sensing mechanism of the graphene-based materials interact with specific analytes also discussed. Graphene and graphene-based materials have shown great potential for detecting gases and humidity due to their high specific surface areas. Quartz crystal microbalance (QCM) sensors have been massively developed because they have high sensitivity, consume low energy, and can be readily modified. Recently, QCM coated by graphene composites has been explored to sensitively and selectively detect various gases and humidity. Herein, we summarize the recent progress on QCM gas sensors and QCM humidity sensors based on graphene materials and graphene composites. We start from an introduction to the sensing principle of QCM, synthesis and preparation of graphene materials used for QCM sensing material, application of graphene materials and graphene composites for sensing materials of QCM gas sensors and humidity sensors, and the mechanism of those sensors. We mainly summarize the recent advances in the performances of QCM gas sensor and QCM humidity sensor coated with pristine graphene, graphene oxide, reduced graphene oxide, and various graphene-based composite materials, including chemical, polymer, metal oxide, and other carbon-based materials. The challenges for future works related to the development of QCM sensors coated by graphene materials or graphene composites are also elaborated.